(untitled) (Tanzania Medical Journal, 2020)
Sickle Cell Disease (SCD) is an inherited disorder of the Haemoglobin molecule of the red blood cells that is associated with serious complications and reduced life expectancy. Over 75% of people with SCD live in Sub-Saharan Africa (SSA), and this proportion are projected to increase to 85% by the year 2050. In Tanzania, approximately 11,000 babies are born with SCD each year, ranking 5th in the world. The high prevalence of SCD in SSA is compounded by the disproportionately higher mortality compared to that observed in the high-income countries. In Tanzania, SCD is a major contributor to under-five mortality and is estimated to account for 7% of all-cause mortality in this age group. Newborn screening (NBS) is the practice of testing babies right after delivery to ascertain whether they have diseases that are potentially lethal if not treated early. Where routinely practiced, NBS has significantly reduced morbidity and mortality associated with such diseases. The Sickle Cell Programme at Muhimbili University of Health and Allied Sciences (MUHAS) in Dar-es-salaam and Bugando Medical Center in Mwanza have both conducted pilot NBS for SCD, showing that the intervention is generally feasible and acceptable in Tanzania. The successful introduction and expansion of NBS in Tanzania will require careful planning and advocacy at community to national level.